Analysis Of Factors That Influence The Intensity Of Tourist Visits On Attractions Emeresa Baths In Bantaeng Regency - Andini, Surya; Akhmad; Anggoro, Yusuf Alfian Rendra (Scimadly Publishing, 2025)
Tourism is one of the main contributors to Indonesia’s foreign exchange, supported by its diverse natural and cultural attractions across the archipelago. Bantaeng Regency in South Sulawesi is among the regions that continues to develop local tourism, with the Eremerasa Natural Bathing Site as one of its leading destinations. Despite its potential, the site faces challenges in maintaining facilities and optimizing promotional strategies to attract more visitors. This study aims to examine the effect of facilities and promotion on the intensity of tourist visits by employing a descriptive quantitative approach using the latest data in 2023. A total of 50 domestic tourists were surveyed through non-probability sampling, with data collected via observation, questionnaires, and documentation, and analyzed using multiple linear regression. The results show that both facilities and promotion have a positive and statistically significant influence on visit intensity. The novelty of this study lies in its focus on a local tourism object in Bantaeng using recent data, offering insights for policymakers and site managers to enhance competitiveness and sustainability of regional tourism.